Electrolyte Levels in Poor Prognosis and Early Neurological Deterioration in Patients With Acute Ischemic Stroke - Shengli Pan; Bohuai Yu; Yilin Chen; Yufan Gao; Wei Xie; Yining Jin; Guoliang Zhou; Jialing Lou; Rui Zhang; Chao Chen; Yiyun Weng; Guangyong Chen (The Journal of Clinical Hypertension)
ABSTRACT Discrepancies in serum electrolyte levels have been observed between stroke patients and healthy individuals. Previous studies have indicated an association between electrolytes and all‐cause mortality as well as cardiovascular events in stroke patients. However, there still lacks comprehensive analysis on the connection between electrolytes and negative outcomes in hypertensive individuals with early neurological deterioration (END). Totally 1341 patients treated with thrombolysis for acute ischemic stroke at the First Affiliated Hospital of Wenzhou Medical University were included. Outcomes included END, 3‐month, 6‐month, and 1‐year poor prognosis. Logistic regression assessed the correlation and restricted cubic spline analysis examined dose‐response relationships. Subgroup analysis validated the relationship between electrolytes and prognosis in hypertensive patients. A total of 242 patients exhibited a 3‐month poor prognosis. Significant differences were observed in Cl−, Ca2+, and Mg2+ levels between mRS binary classification. Logistic regression identified Cl− as the strongest predictor for 3‐month, 6‐month, and 1‐year mRS score and Ca2+ for END. Restricted cubic spline analysis revealed relationships between higher concentrations of Na+ and poorer prognosis. In the hypertension subgroup, a higher concentration of Na+ indicated worse 6‐month and 1‐year outcomes and a lower concentration of Ca2+ was linked to a higher risk of END. The concentration of Na+ is related to adverse clinical outcomes, while that of Cl− and Ca2+ are associated with END. Among hypertensive patients, elevated levels of Na+ and Ca2+ concentration are respectively associated with 6‐month poor prognosis and END. Monitoring the electrolytes may promote the early identification of individuals at high risk of poor functional outcomes.